Information On Financial Performance Of Sharia Commercial Banks And Their Determining Factors - Purnomo, Hadi; Albart, Nicko (Universitas Dharma Wacana, 2023)
The research aims to examine the impact of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR) on the Financial Performance of Return on Assets (ROA) in Sharia Commercial Banks registered with the OJK during 2018-2022. The population in this research is Sharia Commercial Banks registered with the OJK during 2018-2022. A total of 60 data from 12 Sharia Commercial Banks registered with the OJK during 2018-2022, and this is the sample used in this research with sample selection using the purposive sampling method. The data analysis used is descriptive statistics, classical assumption testing and hypothesis testing using the multiple regression analysis method which was tested using SPSS'26 software. The results of this research show that (1) Non-Performing Financing (NPF) does not statistically have a significant influence on profitability (ROA) in Sharia Commercial Banks registered with the OJK during 2018-2022. (2) Capital Adequacy Ratio (CAR) statistically has a significant influence on profitability (ROA) in Sharia Commercial Banks registered with the OJK during 2018-2022.